Perspectives in business informatics research 10th International Conference, BIR 2011, Riga, Latvia, October 6-8, 2011 : proceedings - Grabis, Jānis; Kirikova, Marite (Lecture Notes in Business Information Processing, 2011)
This book constitutes the refereed proceedings of the 10th International Conference on Perspectives in Business Informatics Research (BIR), held in Riga, Latvia, in October 2011. The 25 full papers accepted for this volume were selected from 68 submissions. In addition, two invited papers presented at the conference are also included. The papers have been organized in topical sessions on business intelligence and performance management, data and processes, ontologies, architectures, stakeholders' perspectives, Web information systems and services, and systems approach.